Conversations on conversion : the Hatfield Square case study - Du Toit, Jacques L. (University of Pretoria, 2018)
Following the redevelopment of one of Pretoria’s most prominent social spaces, Hatfield Square, the character of the area surrounding the space is noticeably altered resulting in an apparent change in the perceptions of those who live in the area and who used the space. This study is aimed at understanding what these changes mean for the people (the former users and those familiar with the area) in terms of how they construct meanings around the conversion of Hatfield Square, particularly the impact on their social interactions and their use of the space. A qualitative study was undertaken within an interpretive-, social constructivist paradigm using a case study design combined with elements of phenomenology. Following Glaser’s classic Grounded Theory approach, the case of Hatfield Square was studied by capturing the experiences, opinions and perceptions of former users and allowing a preliminary theory to emerge from the data, namely the loss of unseen social synergy created by this unique space and how the conversion of this space left a void which cannot be filled simply by other functionally similar spaces. Data were managed and analysed using Atlas.ti, a qualitative data analysis software, bringing another dimension to the methodology as the use of qualitative analysis software is still relatively limited in built environment research. During initial data gathering a vast array of potential categories emerged and after distilling these through analysis, further data gathering, refined analysis and directed memoing, a core category emerged. Loss was the central theme in the data, in terms of opportunities, social space and sentimental value. This core of loss led to a comparison to existing literature on the implications of urban spatial change, discourse on changing public spaces, critical social theory and elements of emotional geography. This study has specific focus on the case of Hatfield Square and concludes that despite previous work done on the implications of converting spaces, planners and developers still fail to take cognisance of the unquantifiable social dynamics and fabrics that are equally as part of these spaces as their physical structures. As urban planners our focus is too often fixed on the physical environments and how to understand them in order to improve planning practices and policy. The plans we make and the environments we affect are ultimately for people, and accordingly, their success should be measured by how they function for those people and how they are experienced by their users. By providing increased knowledge on a phenomenon related to development and the change of spatial elements within our city, this study provides the opportunity for decision makers (including those responsible for planning as well as those shaping and implementing policies) to make more informed decisions with holistic views of potential impacts.